Pengaruh Metode Ekstraksi Maserasi dan Ultrasonik Terhadap Aktivitas Antioksidan Daun Beluntas (Pluchea indica L) - Ernoviya Ernoviya; Zulfikri Zulfikri (LPPM Universitas Abdurrab, 2024)
The antioxidant activity of the ethanol extract of beluntas leaves (Pluchea indica L.) was tested using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method. This method is simple, easy to use and short in time. Several plants have used the ultrasonic extraction method for a short time and produced a higher yield than the maceration method. The aim of this research was to determine the effect of extraction methods on the antioxidant activity of beluntas leaves (Pluchea indica L.). This research method is an experimental method that uses beluntas leaves (Pluchea indica L.), extracted using the maceration method for 24 hours and ultrasonics for 30 minutes, 60 minutes. The extraction results were measured for their antioxidant activity using a UV-Vis Spectrophotometer. The results showed that extraction of beluntas leaves (Pluchea indica L.) using the maceration method produced an IC50 of 79.99 Î¼g/ml and sonication for 60 minutes produced an IC50 of 54.29 ug/ml, including the strong category, while the ultrasonic method for 30 minutes produced an IC50 of 48.81 ug/ml. ml is in the very strong category. The conclusion of this research is that the ultrasonic extraction method produces higher antioxidant activity than the maceration method.